1951
DOI: 10.1139/z51-015
|View full text |Cite
|
Sign up to set email alerts
|

PARACUARIA MACDONALDI n.g., n.sp. (FAMILY ACUARIIDAE, SUBFAMILY ACUARIINAE) FROM THE SEA GULL (LARUS ARGENTATUS)

Abstract: Paracuaria macdonaldi n.g., n.sp. (family Acuariidae, subfamily Acuariinae) is described from the sea gull, Larus argentatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
3
0
1

Year Published

1965
1965
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
4
3
0
1
Order By: Relevance
“…The measurements of the specimens in the present study turned out larger that the description by the authors above but are coincident with the description of Rao (1951), who named the parasite as P. macdonaldi (Rao), which is actually considered a synonymous of P. adunca. This species of nematode has been isolated from the proventriculus and under the linning of the gizzard of Charadriiformes and Gaviiformes (Rao, 1951;Anderson & Wong, 1982;Díaz et al, 2004;2011). Under the light microscope, near the middle of the total length of the left spicule, a constriction is present, which is coincident with the division of the spicule to form a tube, as was described by Díaz et al (2004).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The measurements of the specimens in the present study turned out larger that the description by the authors above but are coincident with the description of Rao (1951), who named the parasite as P. macdonaldi (Rao), which is actually considered a synonymous of P. adunca. This species of nematode has been isolated from the proventriculus and under the linning of the gizzard of Charadriiformes and Gaviiformes (Rao, 1951;Anderson & Wong, 1982;Díaz et al, 2004;2011). Under the light microscope, near the middle of the total length of the left spicule, a constriction is present, which is coincident with the division of the spicule to form a tube, as was described by Díaz et al (2004).…”
Section: Discussionsupporting
confidence: 89%
“…The morphological characteristics, including the number of pre-cloacal and post-cloacal papillae, are coincident with the description of Wong & Anderson (1982b) and Díaz et al (2004). The measurements of the specimens in the present study turned out larger that the description by the authors above but are coincident with the description of Rao (1951), who named the parasite as P. macdonaldi (Rao), which is actually considered a synonymous of P. adunca. This species of nematode has been isolated from the proventriculus and under the linning of the gizzard of Charadriiformes and Gaviiformes (Rao, 1951;Anderson & Wong, 1982;Díaz et al, 2004;2011).…”
Section: Discussionsupporting
confidence: 86%
“…The morphological characteristics of the specimens we describe here correspond precisely to Rao's (1951) rather incomplete description of the genus Paracuaria, except with respect to the lateral alae: Rao states "... no lateral alae". Given the great similarity of the remaining generic criteria, we do not feel that the simple presence of lateral alae in our specimens is sufficient to justify a new genus; accordingly it is necessary to redefine the genus Paracuaria as follows:…”
Section: Discussionsupporting
confidence: 61%
“…The family Acuariidae has been considered by Chabaud & Czaplinsky (1961) to be derivable from the Habronematinae because of the structure of the head in the genus Paracuaria Rao, 1951. This I do not accept.…”
Section: The Structure Of the Head In Epomidiostomum (Amidostomidae)mentioning
confidence: 97%
“…In 1963 Chabaud, Brygoo & Durette confirm the placement of Torquatoides when describing T. balanocephala vivipara nov. var., and Chabaud & Czaplinski (1961) redescribe Paracnaria macdonaldi Rao, 1951 and interpret it as a form linking the Habronematinae and Acuariinae. As Chabaud (1960) points out however, "Nous n'avons pas encore eu l'occasion d'etudier le genre Schistorophus Railliet, 1916, ni les genres dont les pseudo-levres se terminent par une pointe apicale" and my study of such forms has shown that they are distinct from the Habronematinae line and are referable to the Acuanidae, which should be retained as a distinct group.…”
mentioning
confidence: 99%